The Effect of Using Rap Songs on Students’ Pronunciation Achievement - Putri Riskiyani Amalia; Wiwiek Eko Bindarti; Zakiyah Tasnim (Pancaran Pendidikan, 2019)
Rap songs could be challenging and interesting media and teaching materials for students to follow the English teaching and learning process, especially pronunciation. The design of this study was a quasi-experimental research with posttest only.  The two classes were chosen as the experimental group and control groups by considering the result of the homogeneity test. The experimental group was given the treatment of English pronunciation using rap songs, while the control group was given conventional treatment using drilling. Posttest was given to both groups. The data were analyzed using non-parametric statistics that is, the Mann-Whitney U test. The sig value of the Mann-Whitney U test by using SPSS software was 0.000 and that was less than 0.05 with 95% of the significance level. It means that the null hypothesis was rejected, thus alternative hypothesis was accepted. It means that there is a significant effect of using rap songs on students’ pronunciation achievement. These results are in line with the statement of some researchers that songs are good factors that could be enjoyed and motivate learners. The learning process that uses rap songs provides a means for teachers to easily incorporate music into their teaching.